Correction to: Fast and accurate pseudoinverse with sparse matrix reordering and incremental approach (Machine Learning, (2020), 109, 12, (2333-2347), 10.1007/s10994-020-05920-5) - Jung, Jinhong; Sael, Lee (Machine Learning, 2021)
The article [Fast and accurate pseudoinverse with sparse matrix reordering and incremental approach], written by [Jinhong Jung and Lee Sael], was originally published Online First without Open Access. After publication in volume [109], issue [12], pages [2333–2347] the author decided to opt for Open Choice and to make the article an Open Access publication.